Assessment of the impact of sand-dust storms on oasis agriculture in arid areas : a case study of Bugur County, Northwest China - Aili, Aishajiang; Shrestha, Rajendra Prasad; Clemente, Roberto S.; Cochar, Roland; IFP - Ford Foundation, USA; Asian Institute of Technology Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2010)
Sand-dust storms are the outcome of interactions between weather process and processes on the ground. The dry lands of the world are affected by moderate to severe land degradation from wind erosion and there is evidence that the frequency of sand -dust storms is increasing. The occurrence of wind erosion at any place is a function of weather events interacting with soil and land management through its effects on soil structure, tilth and vegetation cover. Human induced change is by far the most significant factor in the alarming increase of sand-dust storms in northwest China. In this study, the pattern of sand-dust storms in the Bugur County, Northwest China is presented. The impacts of sand-dust storms were described in terms of crop damage, orchard damage, soil productivity losses, economic losses and livelihoods impacts. Measures to combat sand-dust storms include reduction of the impact of wind speed through the use of shelterbelts; protection of the loose soil particles through the use of crop residues or adjusting farming structure. Future strategies for reducing the impacts of sand-dust storms must be based on community-based approaches that integrate effective crop and land management strategies as well as policy interventions to promote more effective soil conservation measures at the national and regional scales.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science in Natural Resources Management, School of Environment, Resources and Development
Thesis (M.Sc.) - Asian Institute of Technology, 2010
Keywords: Arid regions agriculture -- China, Northwest -- Bugur County; Sandstorms -- China, Northwest -- Bugur County